Diversity and abundance of zooplankton in Medik Reservoir of Turkey - Saler, Serap (Maejo Univ, 2017)
Zooplankton samples were taken monthly from Medik Reservoir between June 2013 - July 2014. A total of 40 species (28 belonging to Rotifera, 8 to Cladocera and 4 to Copepoda) were identified in the reservoir. Rotifers were the dominant group in the reservoir (70%) followed by Cladocera (20%) and Copepoda (10%). Water temperature, pH and dissolved oxygen were measured during field trips. Shannon Wiever species index value was recorded with the highest value being 2.81. The Q Brachionus/Trichocerca index value of 2 indicated that the reservoir was eutrophic.
Keywords: Rotifera; Cladocera; Copepoda; zooplankton; Medik Reservoir; Turkey